KONSELING LOGO THERAPY BAGI LANSIA - Patriana Patriana; Rifqi Muhammad (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
Erderly is the final phase in the stage of human development. In this phase, each individual feels very rapid changes, both changes in the terms of physical, mental, social and psychological. The approach used to help the erderly by using logo therapy counseling. This approach emphasizes the search and awareness of the meaning of life for the client. Logo therapy counseling is expected to help erderly find the meaning of life so that they can live their old age happily. The method used in this study is action research, in the form of individual counseling services that has four stages, namely the introduction and rapport development stage, the problem disclosure stage, the joint discussion stage and the conclusion evaluation stage.